Enhanced socially oriented mission-based driving cycles generation and simulation framework for light electric vehicles - Petr Hajduk; Mikaela Ranta; Mehrnaz Farzam Far; Jenni Pippuri-Mäkeläinen; Joel Anttila; Mario Vukotić; Damijan Miljavec (Humanities & Social Sciences Communications)
Abstract Standard driving cycles are commonly used to assess vehicle performance and to design and optimize vehicle powertrains. However, these standard driving cycles lack some details, especially regarding slopes, curves, traffic variability, or weather conditions. Therefore, more realistic driving cycles are required to customize the powertrain and to optimize a vehicle’s energy usage according to its mission and users’ needs. This paper presents a mission-based methodology for generating local driving cycles while considering various terrain profiles, driving conditions, and traffic dynamics. The presented methodology applies to any category of vehicles and geographical locations. Nevertheless, we showcase this methodology using commercial and private electric heavy quadricycles in urban areas of two different European cities: Helsinki, Finland, and Regensburg, Germany, which have different terrain profiles, traffic dynamics, and daily routines/needs of the residents. The generated driving cycles are used to define the electric energy consumption and charging requirements of the vehicle. To demonstrate the effectiveness of our method, we compare the performance of the proposed driving cycles against the World Motorcycle Test Cycle (WMTC), which is a standardized test cycle for light electric vehicles. These results demonstrate that the geographical, historical and cultural context of a city (city’s configuration combined with its inhabitants’ habits) significantly influences powertrain and battery specifications. Specifically, the proposed methodology captures a much wider variation in energy consumption outcomes compared to WMTC. These findings emphasize the importance of tailoring driving cycles to specific geographical conditions and intended missions to ensure accurate powertrain sizing and optimize efficiency.